Industrial symbiosis as the base for implementing circular economy - Leite, Janaína de Souza (2023)
This work evaluated the use of Industrial Symbiosis (IS), and the importance of partnerships, as base for implementing the Circular Economy. For that purpose, action research was used and the stakeholders were grouped in a project called LABMOB. The study analyzed mainly noble wood and its use in furniture. A questionnaire was developed to propose a possible business model. The main results are the closing of cycles and the recovery, with upcycling, of noble wood and a series of other discarded materials, such as metals, in addition of exclusive products, therefore with high added value was obtained. Other advantages are the formation of a wide network that has a micro (designers), meso (national companies) and macro (international organizations) characters. There is also the achievement of an almost spontaneous process that, although initially parasitic, proved to be disjunctive (mutualistic) in the end. For an adequate business model, one must consider reaching an environmentally aware public with good purchasing power, which makes the figure of the designer extremely important. The use of noble wood in such conditions is still scarce, being common only its disposal through burning, to obtain energy.